Schistobrachia kabata sp. nov. (Siphonostomatoida: Lernaeopodidae) from rajiform hosts off South Africa - Dippenaar, Susan M. (Zootaxa, 2016)
The genus Schistobrachia Kabata, 1964 (Lernaeopodidae: Siphonostomatoida) currently accommodates five species of which two infect holocephalans and three utilize elasmobranchs. Kensley & Grindley (1973) reported three females from “Dipturus batis” (Linnaeus, 1758) collected in Table Bay, South Africa, which they assigned to S. ramosa (Krøyer, 1863), a species previously known only from the North Atlantic. Re-examination of these specimens (labelled Charopinus ramosus Krøyer, 1863 and deposited in the Iziko South African Museum) and additional Schistobrachia material newly collected from the gills of various Rajiformes off the South African west and south coasts, showed that Kensley & Grindley’s (1973) earlier record of S. ramosa was misidentified and in reality represents a distinct species, S. kabata sp. nov. Both sexes of the new species are described using light and/or scanning electron microscopy.